Engineering covalent organic frameworks in the modulation of photocatalytic degradation of pollutants under visible light conditions. (December 2021) - Jiménez-Almarza, A.; López-Magano, A.; Cano, R.; Ortín-Rubio, B.; Díaz-García, D.; Gomez-Ruiz, S.; Imaz, I.; Maspoch, D.; Mas-Ballesté, R.; Alemán, J.
Abstract: Mixtures of triphenylamine (TPA) and phenyl phenothiazine (PTH) fragments have been incorporated into a series of extended polyimine structures that have been applied in the photodegradation of pollutants of different nature under visible light irradiation. Results obtained revealed that materials containing PTH as the sole photoactive unit resulted in the most active photocatalytic material in the degradation of polybrominated diphenyl ether-1 and Sudan Red III. In contrast, the covalent organic framework containing only TPA acted as the best photocatalyst for the degradation of Methylene Blue. These different trends are related to the versatility of PTH moiety to trigger both photoredox and energy transfer processes, while TPA is only an effective energy transfer catalyst. Highlights: Incorporation of photoactive triphenylamine and phenyl phenothiazine into covalent organic framework structures is shown. This is as an effective approach to direct and modulate the photocatalytic activity of covalent organic frameworks. Photocatalytic degradation of polybrominated diphenyl ether-1, Sudan Red III and Methylene Blue is achieved. These materials have distinct photophysical properties that trigger different mechanistic pathways.